2018
DOI: 10.1021/acs.joc.8b02354
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Oxidation of Enol Derivatives to α-Alkoxy Carbonyls Using Iminium Salt Catalysts: A Synthetic and Computational Study

Abstract: We report herein the first examples of asymmetric oxidation of enol ether and ester substrates using iminium salt organocatalysis, affording moderate to excellent enantioselectivities of up to 98% ee for tetralone-derived substrates in the -hydroxyketone products. A comprehensive density functional theory study was undertaken to interpret the competing diastereoisomeric transition states in this example in order to identify the origins of enantioselectivity. The calculations, performed at the B3LYP/6-31G(D) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…This oxaziridinium formation is thought to be diastereoselective. [25] Nucleophilic attack on the oxaziridinium by the phenolate gives rise to the o-quinol, in the enantiodetermining step of the reaction. The o-quinol then dimerizes in a regio-and diastereoselective manner, [26] giving rise to the bicyclo[2.2.2]octenone product.…”
Section: Methodsmentioning
confidence: 99%
“…This oxaziridinium formation is thought to be diastereoselective. [25] Nucleophilic attack on the oxaziridinium by the phenolate gives rise to the o-quinol, in the enantiodetermining step of the reaction. The o-quinol then dimerizes in a regio-and diastereoselective manner, [26] giving rise to the bicyclo[2.2.2]octenone product.…”
Section: Methodsmentioning
confidence: 99%
“…In a related study, Jones and co-workers explored the epoxidation and hydroxylation of cyclic vinyl phosphate acetate and trialkylsilyl ethers. They observed that vinyl phosphate and trialkylsilyl ethers performed significantly worse than the corresponding vinyl acetate [ 214 ].…”
Section: Oxidation and Reduction Reactions Of Organophosphatesmentioning
confidence: 99%
“…The authors have cited additional references within the Supporting Information. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Supporting Informationmentioning
confidence: 99%